A 100 year perspective on the life history of coastal cod (Gadus morhua) from the Søndeledfjord in Skagerrak - Lund, Marthe Bråthen (2008)
Many fish stocks today are declining due to the heavy harvesting and the increasingly demand for more food caused by the growing human population. Life-history trait as age and size at maturity are affected, the fish are getting smaller and younger at maturity. The selection is caused by genotypic selection and or phenotypic plasticity. A problem with this investigation is that few scientific surveys cover no more then a few decades. It is not known when the selection started and there is a danger of adopting a “shifting baseline”. In this study a small selection of the Skagerrak cod (Gadus morhua), situated in the Søndeledfjord were studied. The data was sampled in November 2006 by repeating a study done in 1905 by Dahl and Dannevig. The cod data from 2006 was compared with the data from 1905, to see if there were any change in the size and age at maturity. By comparing todays` data with data sampled 100 a years ago, the baseline might be more correct. The data were sampled by accompanying a local fisherman using eel-pot as traps. I predicted that the cod would mature earlier today because of the high exploitation rate the cod has experienced. The results showed the opposite, hence they are maturing later today. They are bigger and older at maturity and they grow faster. Catch-per-unit-effort data also indicate that there might be less fishing today than in 1905. The results might indicate that the decrease in fishing activity resulted in stronger natural selection and increased growth. Phenotypic plasticity may also contribute to the increased growth, due to the less intraspesific competition after the heavy fishing. The trade-off between growth and reproduction, leads to later maturation. The changes could have been difficult to spot if the comparative data were relatively fresh. Hence it was advantageous and helpful to the study’s integrity that the data from the original study was a 100 years old. These results indicate that the cod in the Søndeledfjord may be living in better conditions and that the ...